Seroprevalence of Strongyloides stercoralis in a South Australian Vietnam veteran cohort - Hany Rahmanian; Alexander C. MacFarlane; Karen E. Rowland; Lloyd J. Einsiedel; Susan J. Neuhaus (Elsevier, 2015)
Abstract Objectives: Strongyloides stercoralis is a parasitic roundworm causing chronic infection that is endemic in Southeast Asia. Vietnam veterans are considered to be at high risk of Strongyloides infection. The prevalence of persistent infection in this group is unknown. This study aimed to establish the seropositivity rate of Strongyloides antibodies in South Australian Vietnam veterans and to identify the most reported symptoms within the seropositive group. Method: This cross‐sectional study recruited 309 veterans who had served in Vietnamese territory between 1962 and 1975 and were currently resident in South Australia. Participants completed a self‐administered questionnaire examining demographics, deployment, somatic symptoms and depression. Venous blood was collected for Strongyloides serology and eosinophil count. Participants who demonstrated positive Strongyloides serology underwent faecal microscopy for parasites. Results: A total of 309 participants were recruited and 256 completed the questionnaire. Strongyloides seropositivity was demonstrated in 29 of 249 participants (11.6%). No participant had Strongyloides larvae detected by faecal microscopy. On multivariate analysis, only dermatological symptoms were associated with positive serology (OR 4.84, 95%CI 1.31-17.92, p‐value 0.01). Conclusions: This study found a high seroprevalence (11.6%) of Strongyloides antibodies within the Vietnam veteran community in South Australia. Seropositivity was associated with increased likelihood of dermatological symptoms. Implications: Post‐deployment screening and eradication therapy for Strongyloides should be offered to ADF staff after service in Strongyloides‐endemic areas. This should include those veterans who left the service many years ago.